TÜRKİYE'DE LİSE TARİH ÖĞRETİMİNDE ERMENİ SORUNU VE TEHCİR (1950-2015). - TURAN, Refik (Electronic Turkish Studies)
The objective of this study is to reveal the approach towards the subjects regarding the Armenian, particularly the Armenian question and relocation, in history curricula and history textbooks applied in high schools in Turkey from the beginning of the 1950s up to today. The general survey model and document analysis method were used in this research. As a result of this research we find out that it has been in two phases in general to reflect the Armenian question and relocation issues in history curricula and textbooks in high schools in Turkey. In the first phase, in return for the efforts of ASALA terrorist organization intensifying in the 1970's to bring up the Armenian question to the agenda of the world by assassinating the Turkish diplomats, it has been aimed to raise awareness in the students by including the issues related to the Armenian question into Turkish Republic Revolution History curriculum in 1981 and high school 3rd class History lesson curriculum in 1983. Although the acts of ASALA terrorist organization ended as of the mid 1980s, the Diaspora and the Republic of Armenia that try to keep the Armenian question current in world's agenda started to follow the politics of making the parliaments of many countries accept the claims that a genocide was carried out against the Armenians in 1915. Moreover, these proposals were accepted by many countries, and lastly French Parliament, during 1990s. In response all these manipulation efforts, Ministry of Education Board made a decision on adding subjects related to the Armenian question more detail in history lesson curricula in 2002. A broader space started to be allocated to the subjects of the Armenian question and relocation in history textbooks following this decision. In history textbooks from the 1980's to today, it is seen that the Armenian question, relocation and other information related to the Armenians has increased in parallel with the efforts to popularize the Armenian claims, the language used and style have become tougher.